2021
DOI: 10.1007/s11604-021-01218-1
|View full text |Cite
|
Sign up to set email alerts
|

Particle therapy using protons or carbon ions for cancer patients with cardiac implantable electronic devices (CIED): a retrospective multi-institutional study

Abstract: Purpose To evaluate the outcomes of particle therapy in cancer patients with cardiac implantable electronic devices (CIEDs). Materials and methods From April 2001 to March 2013, 19,585 patients were treated with proton beam therapy (PBT) or carbon ion therapy (CIT) at 8 institutions. Of these, 69 patients (0.4%, PBT 46, CIT 22, and PBT + CIT 1) with CIEDs (64 pacemakers, 4 implantable cardioverter defibrillators, and 1 with a cardiac resynchronization ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…In the Matsubara Letter to the Editor [3], they stated that: (a) if the same physical dose is irradiated, carbon ion therapy (CIT) is safer than proton beam therapy (PBT) even without considering relative biological effectiveness (RBE), because the number of particles itself and the generated number of secondary neutrons are much smaller in CIT, (b) the reaction cross section of the neutron beam production is larger for carbon beams, CIT is still safer than PBT, however. We agree with their observation as we described: "Also, the previous dosimetric studies suggested that CIT generates fewer secondary neutrons than PBT even for the same physical absorbed dose in Gy" referring to the Matsubara et al paper in the Discussion section of the original paper [1]. However, probably due to our insufficient explanation, our phrasing seems to have been too vague to be understood correctly.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In the Matsubara Letter to the Editor [3], they stated that: (a) if the same physical dose is irradiated, carbon ion therapy (CIT) is safer than proton beam therapy (PBT) even without considering relative biological effectiveness (RBE), because the number of particles itself and the generated number of secondary neutrons are much smaller in CIT, (b) the reaction cross section of the neutron beam production is larger for carbon beams, CIT is still safer than PBT, however. We agree with their observation as we described: "Also, the previous dosimetric studies suggested that CIT generates fewer secondary neutrons than PBT even for the same physical absorbed dose in Gy" referring to the Matsubara et al paper in the Discussion section of the original paper [1]. However, probably due to our insufficient explanation, our phrasing seems to have been too vague to be understood correctly.…”
supporting
confidence: 88%
“…To the Editor, We are grateful for the detailed and valuable comments in response to our article [1]. We cited the report of Matsubara et al in the original paper, where they describe the probability of developing cardiac implantable electronic device (CIED) errors [2].…”
mentioning
confidence: 99%
“…15/81 (18.5%) patients with this information available were pacing-dependent. Except for one study that did not provide these data [ 33 ], dose constraints to the CIED’s power generator were maintained within the manufacturer and guidelines recommended limits by all the other studies (maximum dose of 2 Gy (RBE) or less) and the CIED was never located within the treatment field. Hashimoto et al [ 33 ] did not provide information concerning CIED checking and intrasession monitoring; in contrast, in the remaining studies, each CIED was checked in advance before the first session.…”
Section: Resultsmentioning
confidence: 99%
“…Five retrospective [29][30][31][32][33] cohort studies published between 2008 and 2021 were included. A total of 157 patients (age range between 43 and 97 years old) who underwent 161 courses or particle-beam RT were included in the studies.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation